Retiree Health Insurance and the Labor Force Behavior of Older Men in the 1990s - Blau, David M.; Gilleskie, Donna B. (The Review of Economics and Statistics, 2001)
We estimate the impact of employer-provided retiree health insurance (EPRHI) on the labor force transitions of men aged 51 to 62.Data from the Health and Retirement Survey provide detailed and accurate measures of retiree health insurance. Availability of EPRHI increases the rate of exit from employment by two percentage points per year if the individual shares the cost of the insurance with the firm, and by six percentage points if the firm pays the entire cost. The impact of cost-shared EPRHI on the annual rate of labor force exit increases with age, reaching 7.5 percentage points by age 61.